Digital Marketing as a Communication Strategy @Akaalshopbdg in Increasing the Zero Waste Lifestyle of Bandung Society - Hikmah Hamidah; Ummu Salamah; Annisa Husnusyifa (Sean Institute, 2025)
This study examines the effectiveness of digital marketing as a communication strategy for the Instagram account @akaalshopbdg to educate and encourage the people of Bandung to adopt a zero-waste lifestyle. This study also aims to assess the extent to which digital marketing can play a role in increasing the interest and awareness of the people of Bandung to start implementing a low-waste lifestyle. The methods used in this study are qualitative and content analysis methods. With in-depth interviews with the owner and content creators to understand how the communication strategy is designed and how to implement it through digital marketing. The results of the study show that the effectiveness of digital marketing and a good and planned communication strategy are very influential in increasing awareness and interest in changing the zero-waste lifestyle of the people of Bandung. In addition, interactive educational content and two-way communication are needed to attract consumers emotionally, as well as consistent visual content and incentive strategies by creating product bundling can attract more interest significantly and are able to increase awareness and educate the people of Bandung to adopt a zero-waste lifestyle. These findings confirm that digital marketing is not only effective in good marketing but is also able to provide insight into building social behavior towards environmental change. This research is able to provide an important contribution to UMKM who are developing good and effective digital marketing that also has a social impact.